Entirely Emmie - Libenson, Terri (Libenson, Terri. Emmie & friends, 2025)
"These days, Emmie doesn't feel so invisible. At least not around her best friends and her crush, Tyler. Class-clown Joe's jokes aren't landing the way they used to. Who doesn't love a good prank? Apparently not his so-called friends, who don't even seem to care if he's around. When their class goes on an end-of-year camping trip, Emmie and Joe find themselves stuck together--and expect the worst. Butwhat happens instead turns out to be entirely unexpected"--